Pengembangan Media Pop-Up Book Berbasis Strategi Reciprocal Teaching untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V SD pada Mata Pelajaran IPAS - Nurbaetullah Karnita; Liyana Sunanto (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to systematically review research findings concerning the development of pop-up book media based on the reciprocal teaching strategy to enhance elementary school students’ critical thinking skills, particularly in the subject of Natural and Social Sciences (IPAS). The research method employed is a Systematic Literature Review (SLR) using data sources from Google Scholar and the Directory of Open Access Journals (DOAJ), covering studies published between 2020 and 2025. The selection process involved identification, screening, and synthesis of ten relevant articles that met the inclusion criteria: studies focusing on elementary education, the use of pop-up book media or reciprocal teaching strategy, and assessment of critical thinking skills. The synthesis results indicate that pop-up books effectively improve conceptual understanding and learning motivation through contextual three-dimensional visualization. Meanwhile, the reciprocal teaching strategy promotes higher-order thinking skills through its four phases: predicting, questioning, clarifying, and summarizing. The integration of both approaches creates a meaningful synergy that fosters active, collaborative, and engaging learning experiences. This study recommends developing an interactive digital pop-up book integrated with the reciprocal teaching stages to support IPAS learning aligned with the principles of the Merdeka Curriculum. Keywords: Pop-up Book Media; Reciprocal Teaching Strategy; Critical Thinking Skills; IPAS; Elementary School. Abstrak Penelitian ini bertujuan untuk meninjau secara sistematis hasil-hasil studi yang membahas pengembangan media pop-up book berbasis strategi reciprocal teaching dalam meningkatkan kemampuan berpikir kritis siswa sekolah dasar, khususnya pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS). Metode yang digunakan adalah Systematic Literature Review (SLR) dengan sumber data dari Google Scholar dan Directory of Open Access Journals (DOAJ) pada rentang tahun 2020–2025. Proses seleksi dilakukan melalui tahap identifikasi, penyaringan, dan analisis sintesis terhadap 10 artikel yang memenuhi kriteria inklusi, yaitu penelitian dengan konteks pembelajaran SD, penggunaan media pop-up book atau strategi reciprocal teaching, serta pengukuran kemampuan berpikir kritis. Hasil sintesis menunjukkan bahwa media pop-up book efektif dalam meningkatkan pemahaman konseptual dan motivasi belajar melalui visualisasi tiga dimensi yang kontekstual. Sementara itu, strategi reciprocal teaching terbukti mampu mengembangkan keterampilan berpikir tingkat tinggi melalui tahapan predicting, questioning, clarifying, dan summarizing. Integrasi kedua pendekatan ini menghasilkan sinergi yang signifikan dalam membangun pembelajaran aktif, kolaboratif, dan bermakna. Penelitian ini merekomendasikan pengembangan media pop-up book berbasis digital interaktif yang dipadukan dengan tahapan reciprocal teaching untuk mendukung pelaksanaan pembelajaran IPAS sesuai prinsip Kurikulum Merdeka. Kata Kunci: Media Pop-up Book; Strategi Reciprocal Teaching; Kemampuan Berpikir Kritis; IPAS; Sekolah Dasar.